(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The present investigation, the successful preparation of pure ZnO (Z1) NPs and SrBa dual doped ZnO (Z2) NPs by chemical co-precipitation technique without use of any capping agent. The structural and morphological properties of Z1 and Z2 NPs were analyzed using X-ray diffraction (XRD) studies, Field emission scanning electron microscopy (FESEM), Elemental analysis (EDAX), Fourier transform infrared spectroscopy (FTIR). An optical property was studied by UV–Vis spectroscopy and Photoluminescence (PL) spectra. The antimicrobial activity of Z1 and Z2 NPs has been investigated against Staphylococcus aureus and Klebsiella pneumoniae bacterial strains. It has been interestingly observed that Z2 NPs has enhanced the inhibitory activity than that of Z1 NPs against S. aureus and more efficiently than the K. pneumoniae bacterial strain.